TMIC-03. TUMOR INFILTRATING LYMPHOCYTES IN BRAIN METASTASIS: CLINICOPATHOLOGICAL EVALUATION AND COMPARISON WITH PAIRED PRIMARY. (14th November 2022) - Sahay, Ayushi; Indave, Mayur; Chatterjee, Abhishek; Moiyadi, Aliasgar; Patil, Vijay; Gupta, Tejpal; Shetty, Prakash; Singh, Vikas; Menon, Nandini; Sahu, Arpita; Chaudhari, Amit; Sridhar, Epari
Abstract: INTRODUCTION: Little is known about tumour-infiltrating lymphocytes (TILs) in brain metastasis (BM) and their utility as predictive biomarker for immunotherapy. AIM: To analyze TILs in BM, and correlate with corresponding paired primary (PP). METHODS: Inclusion: Histologically confirmed BM and PP (2015-2020). Exclusion: Hematological malignancies, spinal cord/meningeal metastasis, pediatric age, slides/blocks not available. Final Nf 277 BM; 64 PP. One H&E slide from both PP &BM assessed for stromal TILs (sTILs) and intratumoral TILs (iTILs) as per International TIL Working Group guidelines. RESULTS: Median sTILs (10%) were significantly higher than iTILs (1%) in primary and BM (p-value < 0.001). sTILs were mild (<10%) in majority of primary (57.8%) and BM (59.9%), while iTILs were nearly always mild (primary 97.1%; BM 96.9%). Between PP and BM, no change in sTIL category in 48.43%, while conversion in 51.56%, with higher to lower conversion (66.67%) > lower to higher (33.33%). Conversion rate higher for breast (54.3%) &GIT (62.5%) than lung (45.5%) &GUT (40%). In BM, preoperative steroid therapy (PST) showed lower sTILs (≤10%) (p-value= 0.041), and adenocarcinoma histology higher sTILs ( >10%) (p-value= 0.001), while precocious metastasis (p-value= 0.051) and absence of extracranial metastasis (p-value= 0.083) trended towards higher sTILs. Median survival of whole cohort was 20 months (95% CI 14.4-25.68 months). Presence of extracranial metastasis (p-value= 0.01); precocious BM (p-value= 0.007) showed lower overall survival (OS), while adenocarcinoma histology better OS (p-value= 0.029), in both univariate and multivariate analysis. Absence of PST showed longer median survival, though not significant (24.1 vs 19.8months; p-value= 0.19). CONCLUSIONS: sTILs predominantly show high >low conversion between PP and BM, signifying lowered immune response in BM. Thus, evaluation of sTILs in BM, wherever tissue available, may be indicated if immunotherapy is considered. Parameters with higher sTILs showed longer survival, possibly indicating prognostic role of tumor microenvironment in BM.